Building Synergy To Develop Village Tourism Potential: Evidence From Banyumas District, Central Java Indonesia - Pamuji, Kadar; Nasihuddin, Abdul Aziz; Ardanariswari, Riris; Supriyanto, Supriyanto; Rosyadi, Slamet (Faculty of Law, Universitas Jenderal Soedirman, 2019)
An effort to develop village tourism potential is not a simple issue. This development requires careful planning and proper management. The purpose of this research is to formulate a synergy model that engages the village government and village consultative agency elements in the development of village tourism potential. This study takes Baturraden Sub-District, Banyumas Regency, as its research location. Baturraden Sub-District boasts a famous tourism destination, Baturraden Tourist Attraction, and 12 (twelve) villages with tourism potential in its surroundings. In this case, the village government (Pemdes) and Village Consultative Agency (BPD) play a vital role in building synergy to arrange a village tourism potential exploration policy. This legal research employs a qualitative approach, combined interview to collect the data, FGD, a document study, and observation. The research results find that BPD, which takes its role in village discussion, attempts to explore and develop village tourism potential by engaging all stakeholders.Â Keywords:synergy, village consultative agency, village government, village tourism